State Borders as Center of Economic Growth: Case Study of the East Arso District in the Indonesia – Papua New Guinea Border - Paulus Mandibondibo; Suzanna Wanggai; Johni Korwa; Yulius Lada; Galuh Putri Utami; Barrisen Rumabar; Didin Hardiansyah (Papua Journal of Diplomacy and International Relations, 2022)
This article aims to pinpoint the East Arso District’s existing economic conditions and identify factors contributing to devising the region as the center of economic growth in the Indonesia–Papua New Guinea (PNG) border. Data were collected through focus group discussion, observation, and a literature review conducted between October and November 2021. By using a qualitative approach, this study found that the East Arso District offers the potential to be developed as the center of economic growth in the Indonesia–PNG border. The region community’s commodities are considered including agriculture, forestry, fisheries, and livestock goods. The scope of the study also examines the condition of PNG’s neighboring communities in Sandaun Province, road infrastructure, and cross-border and security. This article proposes a model of economic development for the East Arso District: the establishment of Transnational Border Posts (PLBN), border market, road infrastructure, a multi-purpose cooperative society and improvement of access to commodities, education, and health. Additionally, the plans to create the East Arso district the center of economic growth are also expected to strengthen ties and cooperation between Indonesia and PNG, which, in turn, can prevent misunderstanding and conflict in the future. KEYWORDSBorder; East Arso; Indonesia; Keerom; PNG